2010
DOI: 10.1093/nar/gkp1247
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress triggers the preferential assembly of base excision repair complexes on open chromatin regions

Abstract: How DNA repair machineries detect and access, within the context of chromatin, lesions inducing little or no distortion of the DNA structure is a poorly understood process. Removal of oxidized bases is initiated by a DNA glycosylase that recognises and excises the damaged base, initiating the base excision repair (BER) pathway. We show that upon induction of 8-oxoguanine, a mutagenic product of guanine oxidation, the mammalian 8-oxoguanine DNA glycosylase OGG1 is recruited together with other proteins involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 65 publications
14
103
0
Order By: Relevance
“…2 and 3). Those particular nuclear subdomains where OGG1 accumulates most likely represent regions where BER of 8-oxoG takes place (18,28). The data presented here demonstrate that the interaction of XRCC1 with the DNA glycosylase is necessary for the recruitment of the scaffolding protein to the BER pathway (6,22).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…2 and 3). Those particular nuclear subdomains where OGG1 accumulates most likely represent regions where BER of 8-oxoG takes place (18,28). The data presented here demonstrate that the interaction of XRCC1 with the DNA glycosylase is necessary for the recruitment of the scaffolding protein to the BER pathway (6,22).…”
Section: Discussionmentioning
confidence: 67%
“…We have previously shown that after induction of oxidative DNA damage, OGG1 is recruited to chromatin, together with other BER proteins such as APE1, XRCC1, and LIG3 (18,28). The BER-specific recruitment of repair factors can be distinguished from the recruitment to SSBR through several criteria related to their relocalization within the nucleus: (i) the kinetics of formation of detergent-resistant foci or patches; (ii) their morphological parameters, such as size and circularity; and (iii) the requirement of PARP1 activity for their assembly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The access-repair-restore theory proposed by Smerdon 54 showed that oxidative stress and other environment injuries can cause recruitment of DNA repair complexes preferentially to open chromatin regions. [55][56][57] Additionally, an opened chromatin configuration caused by DNA damage might explain the "stem cell like" characteristics identified in pre-malignant 4C cells. The repair factors could then recruit chromatin remodeling proteins, histone modifying enzymes as well as DNMTs to DNA lesion in order to repress transcription and stop possible sequence reading errors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…47,48 There is clear evidence that the chromatin structure can hinder the initial steps of BER. 49,50 Although glycosylase activity (UNG2 and SMUG1) is indeed reduced on reconstituted nucleosomes, the complete BER cascade, including APE1, Polb, and DNA ligase III was found to be functional. 44 Recently it was shown that UDG and APE1 are able to interact with an uracil in a nucleosomal construct when the lesion is accessible from the outside, but recognition is hampered if the lesion is shielded by the histone core.…”
Section: Repair In Chromatinmentioning
confidence: 99%